Bank CEOs Characteristics, Compensation Policies, and Impacts on Bank Performance - Curi, Claudia (SpringerBriefs in Finance,, 2018)
This book thoroughly explores the characteristics and importance of bank CEOs against the backdrop of growing awareness of the social implications of CEO behavior for the performance and stability of the financial and economic system. After an introductory section on the relevance of CEOs in the banking industry, the connections between the bank CEO labor market, contractual incentives, and compensation structures are examined. The focus then turns to empirical findings concerning the impact that bank CEO compensation has on various firm-level outcomes, such as bank performance and strategies. In addition, the relation between CEO turnover and changes in compensation policies since the financial crisis is discussed. A concluding section presents some fresh empirical evidence deriving from an up-to-date database of traits of CEOs operating in the largest European banks. For PhD students and academics, the surveys offer detailed roadmaps on the empirical research landscape and provide suggestions for future work. The writing style ensures that the content will be readily accessible to all industry practitioners. .